2012
DOI: 10.1017/s0014479712000427
|View full text |Cite
|
Sign up to set email alerts
|

COMPARATIVE PHOTOSYNTHESIS, WATER RELATIONS, GROWTH AND SURVIVAL RATES IN JUVENILE CRIOLLO CACAO CULTIVARS (THEOBROMA CACAO) DURING DRY AND WET SEASONS

Abstract: SUMMARYThis study deals with the ecophysiological response of Criollo cacao cultivars to water deficit during initial establishment phase in an agroforestry system under shade of four timber species using a randomised block design. CO2 assimilation rate (A), transpiration (E) and stomatal conductance (gs), water potentials, pressure–volume curves and fluorescence measurements were studied during two dry and wet seasons. Survival rates, basal diameter and leaf concentrations of K, P and N were also determined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
40
2
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 20 publications
21
40
2
11
Order By: Relevance
“…Water status. High values of Ψ early in the morning were in agreement to those reported for young plants in well-watered conditions in an agroforestry system (Jaimez et al 2008;Tezara et al 2009;Araque et al 2012) and in young trees in a germplasm bank (Pereyra 2007;Ávila-Lovera et al 2016). By the time of the study (November and January) when monthly rainfall average was high, Ψ at noon of these trees indicated a low transpiration rate which may well be the result of an environment of low evaporative demand.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Water status. High values of Ψ early in the morning were in agreement to those reported for young plants in well-watered conditions in an agroforestry system (Jaimez et al 2008;Tezara et al 2009;Araque et al 2012) and in young trees in a germplasm bank (Pereyra 2007;Ávila-Lovera et al 2016). By the time of the study (November and January) when monthly rainfall average was high, Ψ at noon of these trees indicated a low transpiration rate which may well be the result of an environment of low evaporative demand.…”
Section: Discussionsupporting
confidence: 89%
“…The WUE shown by the two types of cocoa were similar to those reported for younger individuals of six cultivars from Margarita Island and eastern Venezuela grown in a germplasm bank (Pereyra 2007;Tezara et al 2009) but higher than other four cultivars of Criollo cocoa in a agroforestry system (Araque et al 2012). The long-term WUE estimated by δ 13 C in adult trees (-29.2 ‰) was similar to those found in Criollo cultivars (Ávila-Lovera et al 2016) and significantly higher to that reported for younger cocoa trees (-30 ‰) (Pereyra 2007;Tezara et al 2009), indicating that adult trees could even present a better physiological performance during the rainy season.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations